2007
DOI: 10.1177/0272431606294830
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Biosocial Models of Adolescent Cigarette and Alcohol Involvement

Abstract: We tested biosocial models that posit interactions between biological variables (testosterone, estradiol, pubertal status, and pubertal timing) and social context variables (family, peer, school, and neighborhood) in predicting adolescent involvement with cigarettes and alcohol in a sample of 409 adolescents in grades 6 and 8. Models including the biological and contextual variables and their interactions explained significantly more variance in adolescent cigarette and alcohol involvement than did models incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 80 publications
1
27
0
Order By: Relevance
“…However, there was significant modification of aggressive behavior by parentechild relationship [17] and modification of substance use through peer, family, and school context [20]. Vermeersch et al [18] found that peer association moderated the relationship between testosterone and risk taking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was significant modification of aggressive behavior by parentechild relationship [17] and modification of substance use through peer, family, and school context [20]. Vermeersch et al [18] found that peer association moderated the relationship between testosterone and risk taking.…”
Section: Discussionmentioning
confidence: 99%
“…In group B, only one study [20] found a positive association between testosterone and drug use, which increased as the family, peer, neighbor, and school context became more harmful. The other studies did not find associations between testosterone and drug use but did not consider any peer or family context or other potential modifiers of behavior.…”
Section: Included Studiesmentioning
confidence: 99%
“…So, even though the associations between the individual and contextual risks and adolescent substance use have been copiously studied, not many have examined how social contexts may interact with or moderate the role of individual characteristics to shape early substance use. And even though some studies explored the simultaneous contributions of multiple risk factors from multiple ecological levels on adolescent use (Buu et al, 2009), only a handful of reports (Foshee et al, 2007;Hill et al, 2010;Legrand, Keyes, McGue, Iacono, & Krueger, 2008;Scheier et al, 2001) specifically examined person-environment models in relation to adolescent substance use, or asked the question of how different personal characteristics interact with different environments to shape early substance use.…”
Section: Person-environment Interactions and Adolescent Substance Usementioning
confidence: 99%
“…The specific focus was on the putative interactive (i.e., moderating) effects, as such person-environment approaches have been understudied in the etiology of underage substance use (Cleveland, Feinberg, Bontempo, & Greenberg, 2008;Ennett et al, 2008;Foshee et al, 2007); yet they may be vastly more informative-both empirically and theoretically-than the simple main-effects models (Ennett et al, 2008;Foshee et al, 2007). Because such interaction hypotheses have not been extensively tested, it remains largely unclear whether individuals with different temperaments would respond differently to different contextual risks, and, if so, how these risks may interact to impact actual substance use.…”
Section: Aims Of the Current Studymentioning
confidence: 99%
“…Among a sample of suburban middle school students in North Carolina, Foshee et al (2007) found that the effect of pubertal development on cigarette and alcohol use among girls was moderated by peer contexts but not neighborhood contexts. However, Foshee et al (2007) speculate that the lack of observed neighborhood effects in their study may have been due to problems with the validity of their pubertal timing measure. So there is a paucity of empirical research examining the moderating role of neighborhood disadvantage on the association between pubertal development and adolescent girls' substance use, and the available studies have been limited to specific geographic areas, racially and economically homogenous samples, or limited by psychometrically suspect measures.…”
Section: Theory and Previous Researchmentioning
confidence: 95%